La mortalité comme expression de la vulnérabilité humaine face aux catastrophes naturelles : deux inondations récentes en France (Xynthia, var, 2010) - Freddy Vinet; Laurent Boissier; Stéphanie Defossez (VertigO)
This paper analyses the fatalities related to two recent floods in France. The first flood event was a nightly sea surge due to Xynthia windstorm on the Atlantic coast in February 2010 the 28th. The second was a flash flood which struck the department of Var in the French Mediterranean region in June 2010 the 15th. The death tolls are respectively 41 and 26 fatalities. The characteristics of each fatality and the circumstances of death are accurately examined. In the first case, elderly people were surprised while they were sleeping and were drowned in their home. In the case of flash flood the characteristics of victims are diversified ; traffic-related deaths are numerous. The demonstration focuses on the factors that explain mortality : water depth, type of housing, vulnerability of people. The paper concludes discussing the effectiveness of prevention measures and caution messages that must be adapted to natural and human local context (age of people, kind of flood…)